Iskolázatlan szülők gyermekei és roma fiatalok a középiskolában: Seszámoló az Educatio Életpálya-felvételének 2006 és 2009 közötti hullámaiból - Gábor Kertesi; Gábor Kézdi (Hungarian Academy of Sciences, Institute of Economics, 2010)
– The paper looks at secondary school attendance and grade retention after 8th grade in Hungary. It makes use of panel data of the Hungarian Life Course Survey from 2006 through 2009. Three and a half years after finishing 8th grade, ninety per cent of the children are in school, three quarters on the continuous track in 12th grade. The corresponding figures for Roma children are only 60 and 40 per cent, respectively. Drop-outs and grade retentions are especially frequent in vocational training schools and evening schools; quite a few students switch between tracks; and drop-outs and evening school students do not have a second chance on the regular track. Standardized test scores in 8th grade are strong predictors of secondary school career, but the relation is different among the children of Roma and uneducated families, indicating the importance of other factors.
Keywords: J15; I20; 330; Roma minority; secondary school drop-outs; Allgemeinbildende Schule; Bildungsverhalten; Abbrecher; Ethnische Gruppe; Roma-Bevölkerung; Ungarn